Self-Assembly of Embryonic and Two Extraembryonic Stem Cell Types Into Gastrulating Embryo-like Structures. Issue 1 (January 2019) - Sozen, Berna; Amadei, Gianluca; Cox, Andy; Wang, Ran; Na, Ellen; Czukiewska, Sylwia; Chappell, Lia; Voet, Thierry; Michel, Geert; Jing, Naihe; Glover, David M.; Zernicka-Goetz, Magdalena
Abstract : (Abstracted from Nature Cell Biology 2018;20:979–989) Three stem cell types found in the natural embryo differentiate to become 3 distinct tissues: the embryonic tissue or epiblast, the trophectoderm, and the primitive endoderm. Signaling interactions between each of these tissue types are important for morphogenic pathways causing the cell rearrangements of gastrulation and establishing anterior and posterior identity.